Implementation Of the Saw Method in A Decision Support System for Determining Social Assistance Program Recipients: Case Study: Ciluncat Village - Fathuroohman, Irfan; Susanto, Susanto; Suwarno, Adi; Damayanti, Resti Aulia (Electronic, Business, Management and Technology Journal, 2024)
Poverty is a significant global challenge, particularly in Indonesia, that impedes community welfare and the quality of human resources. The village government has initiated several social aid initiatives to tackle this issue; nevertheless, the distribution is frequently misallocated and imprecise. This study seeks to create a web-based decision support system employing the Simple Additive Weighting (SAW) method to improve the accuracy, objectivity, and efficiency of identifying social assistance beneficiaries in Ciluncat Village. The SAW method evaluates alternatives by aggregating the weighted ratings for given qualities. This research uses descriptive analysis for data gathering and Object-Oriented Analysis and Design (OOAD) for system development. The findings demonstrate that applying the SAW technique in Ciluncat Village enhances the efficiency of social assistance distribution, minimizes errors, and expedites the delivery time of aid. This system enables village officials to pick assistance recipients objectively and equitably.